Nicotinic Acetylcholine Receptor Signaling in Neuroprotection (Springer Singapore, 2018)
This open access book presents the roles and mechanisms of signal transduction triggered by nicotinic acetylcholine receptors (nAChRs) stimulation in neuroprotection against toxic effects of risk factors of neurodegenerative diseases. Accumulating evidence suggests that nAChRs in the CNS play important roles not only in excitatory neurotransmission but also in neuronal survival and related functions. Neuroprotection mediated by nAChRs in neurodegenerative diseases such as Alzheimer's disease is the major topic of this book. In response to rapidly evolving areas in clinical and laboratory neuropharmacology and neurochemistry, this volume provides in-depth coverage of neuroprotection in basic research and future developments in the clinical application of effective neuroprotective strategies in neurodegenerative diseases. This work appeals to both basic and clinical researchers in several fields, such as neuroscience, neurology, and pharmacology. This book is published with open access under a CC BY 4.0 license.